Empirical modelling of sugar uptake and water desorption of osmotically dehydrated mango (Mangifera indica L. cv. Carabao) slices - Imbong, Louis Alain Balios (2012.)
Empirical models describing the sugar uptake and water desorption of mango (Mangifera indica L. cv. Carabao) slices as a function of soaking time were derived.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Carabao mango